Atherothrombosis risk factors in patients with chronic obstructive pulmonary disease on oxygen therapy - Diniz dos Santos, Ricardo Luiz; Santos Resende, Elmiro; Honorato Borges Júnior, Laerte; Pafume de Oliveira, Vinicius; Resende Farina, Pedro Henrique (O Mundo da Saúde, 2018)
The objective of the study was to identify risk factors for atherothrombosis in patients with chronic obstructive pulmonary disease on oxygen therapy. 62 patients of the UFU-HC Home Care program were included. COPD was diagnosed through clinical aspects added with an altered spirometry (FEV1/FVC ≤ 0.7 post BD). The following risk factors for atherothrombosis were evaluated: body composition (body weight, BMI, WCI), fasting glucose, plasmatic lipid profile (TC, LDL-C, HDL-C and triglycerides), tobacco use disorder, sedentarism, rest blood pressure, 6-minute walk test, CRP, FEV1, rest HR, hypoxemia and Framingham score. The mean weight (kg) was 59.3 ± 15.3 with a BMI of 24.4 ± 5.5 and WHR of 1.0 ± 0.1. The risk factors: TC, LDL-C, triglycerides, fasting glucose, systemic BP and tobacco use disorder were equally distributed between the groups and only HDL-C was significantly lower in men. The Framingham score was higher and with statistically significant variation in men. The other variables were also equally distributed between men and women, except the FEV1, which was lower in men. It was concluded that men with COPD on oxygen therapy have a higher Framingham score than women. The lower HDL-C and FEV1 in men represents an elevated risk for atherothrombosis. Lower FEV1, higher CRP and hypoxemia were found in the studied population and represent risk factors for atherothrombosis.